Factors Affecting Depression and Anxiety in Diabetic Patients: A Prospective Cohort Study from a Tertiary Care Hospital in Eastern India - Karpha, Kankana; Biswas, Jyotirmoy; Nath, Siddhartha; Dhali, Arkadeep (International Journal of Medical Students, 2023)
This abstract was published in a different venue and it is not being published in this Supplement to avoid duplicate publications. Link to the publication: https://www.sciencedirect.com/science/article/pii/S2049080122017058?via%3Dihub